EFEKTIVITAS PENEGAKAN HUKUM TERHADAP PELAKU PENIMBUNAN BAHAN POKOK - Deforty Jihan Farrun; Muh. Jufri Ahmad (Gapenas Publisher, 2023)
The need for basic commodities is the primary need of the community which has problems with the criminal act of hoarding staples which still often occurs. to get. This has opened a loophole for acts of hoarding of necessities. In resolving these problems, law enforcement action and the imposition of punishment against the perpetrators of hoarding are required. This study uses normative research methods with statutory and conceptual approaches. Law enforcement against hoarding of necessities which explains how law enforcement is against perpetrators of hoarding necessities using applicable regulations, this study aims to find out the punishment that will be received by perpetrators of hoarding necessities and how effective law enforcement is against hoarding necessities